Strategic Human Resource Management in Sports: Leveraging Data from the Shared Economy in the Smart Technology Era - Wen Yi; Peichun Feng; Wenbin Tan; Minxin Li; Taoluo Feng (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The rapid advancement of Internet technology in China has significantly transformed the landscape of social information exchange, injecting innovation and opportunities into the commercial sector. This technological evolution has catalyzed the integration of various industries with Internet technology, fostering the development of a new sharing economy model. Within this context, the sports industry has also witnessed shifts in traditional human resource management practices. The sharing economy model introduces novel characteristics to human resources, influencing the management strategies and operational efficiency of sports organizations. This paper explores how these changes impact the psychological dynamics of human resource management in sports, emphasizing the adaptation of sports organizations to the new intelligent, shared economic environment. The discussion includes an analysis of the fundamental elements and developmental trends of the sharing economy in this tech-driven era, providing insights into the evolving nature of sports management and organizational behavior.